Evaluasi Formatif Pendidikan Kesetaraan Paket C Di SPNF-SKB (Satuan Pendidikan Non Formal-Sanggar Kegiatan Belajar) Kota Serang - Fatimah Az-Zahra; Hani Safitri; Medhisyam Febrio Alghifari; Rahma Yulia; Siti Muslimah Solehati (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
Evaluation is a very important stage when running a program, because there is an assessment stage to measure the success of learning. The formative evaluation model is an evaluation model created by Scriven (1967) saying that formative evaluation is the collection of information with the aim of improving the learning that has been provided. The research methods used are observation, interviews and literature study. The data analysis technique in this research includes descriptive qualitative research. Descriptive research is research obtained through various aspects regarding symptoms or facts, so that the object becomes clearer. Formative evaluation is important according to educators at SKB-SPNF. By carrying out and obtaining results from formative evaluation, it shows the extent to which the level of achievement of students with learning objectives has been determined. Formative evaluation conducted at SKB-SPNF is effective. This can be seen through the process and results given. The results of formative evaluation are beneficial for educators and learners. The benefits for educators, namely being able to know the extent to which the subject matter is mastered and can estimate the results of summative assessments.